Analysis of the Effect of Work Motivation, Competence, Compensation, Workload, and Discipline on Employee Performance (Case Study at PT. Sumber Segara Primadaya (S2P) Cilacap) - Syahreiza, Muhammad; Rachmawati, Erny; Purwidianti, Wida; Pratama, Bima Cinintya; Astuti, Herni Justiana (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the influence of work motivation, competence, compensation, workload, and work discipline on employee performance in the S2P Cilacap environment. The data collection method used convenience sampling and obtained a sample of 100 respondents. Data were collected using a questionnaire which was analyzed using Structural Equation Modeling (SEM) PLS version 3.2. Testing results show that compensation, work discipline, and workload have a positive effect on employee performance, but competence and motivation have no effect. However, this study has limitations due to its focus on one location and limited sample size. The results of the analysis show that 86.8% of the variation in employee performance can be explained by the factors studied, while the remaining 13.2% are other variables such as self-efficacy, organizational culture, and work environment, as well as expanding the scope of research locations, by conducting research This is expected to provide benefits for the company.